Respostas

A melhor resposta!
2014-08-23T14:52:33-03:00
Detalhadamente...
a = 12 + b
a² + 2a - 2b - ab ÷ 3a + 6 => (12 +b)² + 2.(12 + b) - 2b - (12 + b).b ÷ 3.(12+b) + 6 => (144 + 12b + 12b + b²) + 24 + 2b - 2b - 1.(12b + b²) ÷ 36 + 3b + 6 => 144 + 24b + b² + 24 - 12b - b² ÷ 3b + 42 => 12b + 168 ÷ 3b + 42 => 4b + 4 = 0 => b = - 4 ÷ 4 => b = 1

a = 12 + 1 = 13

a² + 2a - 2b - ab ÷ 3a + 6 => (13)² + 2.(13) - 2.(1) - (13).(1) ÷ 3.(13) + 6 => 169 + 26 - 2 - 13 ÷ 39 + 6 => 180 ÷ 45 =

Espero ter ajudado
2 3 2
ajudou bastante mas sem querer marquei a resposta errada como a melhor. Desculpe-me
td bem